Political dynamics of local government reform in a development context: The case of Turkey - SAVAŞKAN, OSMAN (SAGE PUBLICATIONS LTD, 2021)
This article examines the political dynamics of local government reform in Turkey during 2000s and 2010s, showing how the reform was implemented in a way that reproduced central state power. Contributing to debates on the relationship between state rescaling and decentralisation, it argues that the dynamics of electoral politics are key to determining the nature of institutional changes affecting central-local relations. In the Turkish context, decentralisation did not align with the interests of the ruling Justice and Development Party, given that opposition parties could potentially win local elections and control local municipal councils. By questioning the significance of the recent trend of decentralisation and the devolution of authority to lower levels of government in Turkey, this article contributes to the literature on the limits of decentralisation, especially in non-western contexts.
Keywords: Decentralisation; local government; Turkey; state rescaling; electoral politics; STATE; POLICY; DECENTRALIZATION; GOVERNANCE; AKP; TRANSFORMATION; NEOLIBERALISM; DETERMINANTS; MANAGEMENT